Analysis of Changes in Land Function and Social Culture of Community In Benggaila Watershed - Syaf, Hasbullah (Jurnal Ilmiah Membangun Desa dan Pertanian, 2020)
The Benggaila watershed disembogues into Kendari Bay, the upper part was dominated by forest areas and the middle and downstream parts were dominated by residential areas. Its location in the capital city of Southeast Sulawesi causes a very high change in land use and social culture in the watershed. This study aimed to determine changes in land use and community socio-cultural activities in the period 2004 to 2019. The results showed that changes in land use during that year range were very high. Changes from agricultural land and forest to the settlement were 67.4% dominate the other changes. This condition causes a shift in the socio-cultural pattern of society. The people of origin who lived in the downstream and middle of the watershed were moved to the upstream, while the immigrants stayed downstream of the watershed. These changes have also changed the patterns and methods of farming as well as behavior in utilizing forests. Soil and water conservation efforts were carried out by integrating changes in land use and the current social conditions of the community through adequate land planning and the community's mindset in utilizing the land.